2017
DOI: 10.3389/fevo.2017.00056
|View full text |Cite
|
Sign up to set email alerts
|

Marine Invertebrate Larvae Associated with Symbiodinium: A Mutualism from the Start?

Abstract: Symbiodinium are dinoflagellate photosynthetic algae that associate with a diverse array of marine invertebrates, and these relationships are comprehensively documented for adult animal hosts. Conversely, comparatively little is known about the associations during larval development of animal hosts, although four different metazoan phyla (Porifera, Cnidaria, Acoelomorpha, and Mollusca) produce larvae associated with Symbiodinium. These phyla represent considerable diversities in larval forms, manner of symbion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 154 publications
(205 reference statements)
1
25
0
Order By: Relevance
“…The incorporation of the photosymbiont into host cells and continued maintenance of the association involves both the symbiont (Hill & Hill, ; Sachs, Essenberg, & Turcotte, ; Sachs & Wilcox, ) and the host (Baird, Bhagooli, Ralph, & Takahashi, ; Barott, Venn, Perez, Tambutté, & Tresguerres, ; Paxton, Davy, & Weis, ), whereby mixed symbiont communities are winnowed to one or a few dominant Symbiodiniaceae species, either through host selection mechanisms or competition among Symbiodiniaceae species (Bay et al, ; Coffroth et al, ; Dunn & Weis, ; Poland & Coffroth, ; Rodriguez‐Lanetty, Wood‐Charlson, Hollingsworth, Krupp, & Weis, ). The symbiont winnowing process can take much longer than the initial acquisition period (Mies et al, ; Poland & Coffroth, ). For example, metamorphosed recruits of a soft coral continue altering their symbiont communities over the course of multiple years, eventually harbouring communities similar to those found in their parents (Poland & Coffroth, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incorporation of the photosymbiont into host cells and continued maintenance of the association involves both the symbiont (Hill & Hill, ; Sachs, Essenberg, & Turcotte, ; Sachs & Wilcox, ) and the host (Baird, Bhagooli, Ralph, & Takahashi, ; Barott, Venn, Perez, Tambutté, & Tresguerres, ; Paxton, Davy, & Weis, ), whereby mixed symbiont communities are winnowed to one or a few dominant Symbiodiniaceae species, either through host selection mechanisms or competition among Symbiodiniaceae species (Bay et al, ; Coffroth et al, ; Dunn & Weis, ; Poland & Coffroth, ; Rodriguez‐Lanetty, Wood‐Charlson, Hollingsworth, Krupp, & Weis, ). The symbiont winnowing process can take much longer than the initial acquisition period (Mies et al, ; Poland & Coffroth, ). For example, metamorphosed recruits of a soft coral continue altering their symbiont communities over the course of multiple years, eventually harbouring communities similar to those found in their parents (Poland & Coffroth, ).…”
Section: Discussionmentioning
confidence: 99%
“…These disadvantages suggest that delaying photosymbiont acquisition provides benefits to larvae of HA coral species, perhaps explaining the incongruence between theory and natural history. While the consequences of larval acquisition in HA species have been examined (e.g., Yakovleva et al, 2009, Nesa et al, 2012, Suzuki et al, 2013, we lack a complete assessment of the physiological, behavioural and ecological costs and benefits of HA (Mies, Sumida, Rädecker, & Voolstra, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…These authors concluded that while minimal translocation was observed, this was in quantities which would negligibly contribute to larval energetic demands (Kopp et al, 2016). Despite demonstrations of increased lipid utilization and decreased survival in darkness (Harii, Yamamoto, & Hoegh-Guldberg, 2010), and changes in symbiont transcriptome upon larval infection (Mohamed et al, 2019), these data do not prove translocation per se and therefore a recent review of the topic concluded that during the larval phase a "mutualistic relationship cannot be unequivocally confirmed" (Mies, Sumida, Rädecker, & Voolstra, 2017). Additionally, there were no isotopic signatures of feeding found in planulae of Red Sea coral Stylophora pistillata ).…”
mentioning
confidence: 99%
“…Acquiring symbionts horizontally always includes an aposymbiotic life stage present in all photosymbiotic animal lineages, which is usually the larval phase before metamorphosis into juveniles (e.g. Belda‐Baillie et al, ; Weis et al, ; Harrison, ; Pelletreau et al, ; Mies et al, ). Juveniles then successfully take up the symbiont from their environment, but there seems to be little co‐evolution of species with horizontal transmission and their symbiont partners (van Oppen et al, ; Bright & Bulgheresi, ).…”
Section: Evolutionary Genomics Of Photosymbiosesmentioning
confidence: 99%